2018
DOI: 10.1002/ppul.23830
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise test to quantify enzyme replacement response in pediatric Pompe disease

Abstract: CPET is safe for pediatric Pompe patients. ERT may benefit exercise capacity in patients with less advanced disease. Individualized assessment by CPET, 6MWT, and motor function may help ERT adjustment by providing precise quantification of the response to treatment. Additional studies are needed to clarify the benefit of this assessment protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The reported data on the acute and long-term effects of ERT on CPET parameters is especially in IOPD. The safety of exercise and CPET was demonstrated in LOPD [10,24], and we recently demonstrated the feasibility and safety of CPET in five pediatric Pompe disease patients [11].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The reported data on the acute and long-term effects of ERT on CPET parameters is especially in IOPD. The safety of exercise and CPET was demonstrated in LOPD [10,24], and we recently demonstrated the feasibility and safety of CPET in five pediatric Pompe disease patients [11].…”
Section: Discussionmentioning
confidence: 89%
“…Patients' exercise limitations contribute significantly to the patients' perception of impaired well-being. While the focus on metabolic/functional capacity (e.g., cardiopulmonary exercise testing, CPET) in adult late-onset Pompe disease (LOPD) is growing rapidly, the data on pediatric IOPD patients are scarce [10,11]. Our aim was to provide a more objective quantification of the acute and long-term effect of ERT on exercise capacity and explore the possible relationship between the blood enzyme level and exercise capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Pompe Group Size Calculation : The only previous study investigating exercise capacity in children with Pompe disease includes five patients and shows that children with Pompe have a PeakVO 2 between 11.1 and 40.2 ml/kg/min, with a 75%ile of 37.7 ml/kg/min ( 14 ). We have chosen to use the 75%ile to calculate the group size, as we think this value of PeakVO 2 is closest to the PeakVO 2 of our own Pompe children population.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Despite ERT treatment, many Pompe disease patients eventually become ventilator or wheelchair dependent. It is known that patients with Pompe disease has a decreased exercise capacity which is not caused by impaired skeletal muscle glycogenetic capacity but rather by muscle weakness and wasting ( 14 ). A study by van den Berg et al published in 2015 showed that exercise training in adult patients with late onset Pompe disease might be a safe and effective adjuvant therapy for ERT ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ko [12] estimated MCID ranges for GMFM-88 in pediatric CP with a distribution-based approach grounded on effect size (change divided by standard deviation [SD] at enrollment) of 6 months' physical therapy, and determined its correlation to changes in GMFM-66 and Pediatric Evaluation of Disability Inventory mobility (PEDI) scores. GMFM-88 was developed [18] and validated [11] for CP, a nonprogressive motor disability, yet also has precedent (though not yet validation) for use in children and adults with Pompe disease [19,20]. It complements the infant-specific motor measures used in the pivotal IOPD trials of 160L alglucosidase alfa [21,22].…”
Section: Introductionmentioning
confidence: 99%